Part 3-developmental stage: The cornerstone of training. (April 2021) - Rodriguez, Nicole; Craig Liebenson, D.C.; Duncan, Fred
Abstract: This article highlights the second stage of athletic development, the Developmental Stage. In this article we build awareness in growth and maturation, highlighting a 3-stage process through the use of the Khamis-Roche protocol. We covered an introduction to Strength Development for athletes in the developmental stage. Speed Development was addressed in a progressive way to teach critical positions and we introduced ways to assess a developing athlete from ages 12–15.